Design of Trench MIS Field Plate Structure for Edge Termination of GaN Vertical PN Diode - Sung-Hoon Lee; Ho-Young Cha (Micromachines, 2023)
In this study, we developed an analytic model to design a trench metal–insulator–semiconductor (MIS) field plate (FP) structure for the edge termination of a vertical GaN PN diode. The key parameters considered in the trench MIS FP structure include trench depth, MIS dielectric material and thickness, and interface charge density of MIS. The boundary conditions are defined based on the maximum allowed electric field strengths at the dielectric and semiconductor regions. The developed model was validated using TCAD simulations. As an example, a 1 kV GaN vertical PN diode was designed using the optimized FP structure, which exhibited the same breakdown voltage characteristics as an ideal one-dimensional PN diode structure without edge effects. This proposed simple analytic model offers a design guideline for the trench MIS FP for the edge termination of vertical PN diodes, enabling efficient design without the need for extensive TCAD simulations, thus saving significant time and effort.